The Effectiveness of Cherry Leaf Extract (Muntingia calabura L) as an Anti-Bacterial Against Hatchability of Kub Chicken Eggs in Artificial Hatchery - Aulia Rahmad Hasyim; Jonathan Anugrah Lase; Alwiyah Alwiyah; Suroto Suroto; Khairiyah Khairiyah; Mustafa Hutagalung; Siti Maryam Harahap; Khadijah el Ramija; Dian Lestari; Novita Ardiarini; Abubakar Ibrahim (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The present study aimed to determine the effect of cherry leaf extract (Muntingia calabura L) on hatchability of Balitnak Superior Free Range Chickens (KUB) through artificial hatching. The doses of cherry leaf extract used in this study were 0%, 10%, 15% and 20%. The hatching eggs used came from KUB hens that were intensively reared in the poultry house at UPBS BPTP, North Sumatra. The procedures applied in this study were collection of hatching eggs, fumigation of machines and equipment, setting of machines and hatching eggs, egg washing with cherry leaf extract and hatching of eggs for 21 days. During the hatching process, observations were made on predetermined variables. The observed variables were egg shape index, egg weight loss, shell temperature and hatchability. The method used was completely randomized design (CRD) with 4 treatments and 100 replications. The results showed that the hatching egg shape index in this study was 75,77 – 77,05%. The lowest egg weight loss was at P0 (0%), while the largest weight loss was at P2 (15%). The highest hatchability was observed in P1 (10%) at 84%. The most effective P1 treatment resulted in the highest egg hatchability in the present study.